The Sikhs of the Punjab : Unheard Voices of State and Guerrilla Violence - Pettigrew, Joyce J. M., 1946- (London Zed Books Ltd., 1995)
Village people in the Punjab have lived with the terror of conflict between Sikh militants and Indian security forces. This book presents a human portrait of the struggle.
Include Index and Bibliography
Politics in Contemporary Asia
Keywords: Sikhs--Politics and government -- Terrorism -- India--Punjab